Impementasi Web Scraping Pada OJS Dengan Metode CSS Selector - Agus Purnomo (STMIK Budi Darma, 2022)
Reference sources in research and scientific article writing are journals. For reputable international journals, a lot of software has been developed to retrieve meta data for research mapping. To obtain meta data, for the purposes of visualizing research results from national journals, especially Sinta's journal, it still has to be done manually. Researchers must copy and paste one by one the articles they want. In order to facilitate the retrieval of article meta data contained in a sinta journal with the OJS system, the development of an OJS journal scraping web application was carried out. The chosen web scraping method is the CSS Selector. The application is developed with the Python programming language and additional BeautifulSoup, flask and pandas libraries. From the results of testing the OJS scraping application was able to retrieve meta data in the form of title data, abstract, keywords, author, links. Weaknesses found were not being able to retrieve data in journals with the OJS system that had made changes to the non-OJS standard web interface.